2014
DOI: 10.1093/nar/gku726
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DNA-associated proteins inside eukaryotic cells using single-molecule localization microscopy

Abstract: Development of single-molecule localization microscopy techniques has allowed nanometre scale localization accuracy inside cells, permitting the resolution of ultra-fine cell structure and the elucidation of crucial molecular mechanisms. Application of these methodologies to understanding processes underlying DNA replication and repair has been limited to defined in vitro biochemical analysis and prokaryotic cells. In order to expand these techniques to eukaryotic systems, we have further developed a photo-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…Briefly, this method exploits motion blurring to selectively eliminate signals arising from rapidly diffusing molecules, allowing visualisation of low mobility signals derived from DNA-associated molecules (Fig 2F). Previously we reported that low mobility PCNA (mEos3.1-Pcn1) is notably enriched during S phase [27]. Deletion of rad18 significantly reduced the fraction of these molecules (Fig 2F, right), thus confirming that PCNA-K164 ubiquitylation results in increased amounts of loaded PCNA during unperturbed S phase.…”
Section: Resultssupporting
confidence: 74%
“…Briefly, this method exploits motion blurring to selectively eliminate signals arising from rapidly diffusing molecules, allowing visualisation of low mobility signals derived from DNA-associated molecules (Fig 2F). Previously we reported that low mobility PCNA (mEos3.1-Pcn1) is notably enriched during S phase [27]. Deletion of rad18 significantly reduced the fraction of these molecules (Fig 2F, right), thus confirming that PCNA-K164 ubiquitylation results in increased amounts of loaded PCNA during unperturbed S phase.…”
Section: Resultssupporting
confidence: 74%
“…For the FtsZ imaging we used slower acquisition mode to exclude cytosolic FtsZ molecules—as they diffuse much faster than FtsZ built into the ring structures, their point-spread functions are blurred, thus most of the cytosolic FtsZ molecules are not included in further analysis steps. This approach was first used by Etheridge et al in their work [ 32 ]. mEos3.2-A69T molecules were converted by primed conversion, while PAmCherry was photoactivated using UV.…”
Section: Methodsmentioning
confidence: 99%
“…Although no changes in dissociation time were observed (Extended Data Figures 9b,c), trajectories were likely truncated by photobleaching (our mean trajectory lengths were 8-11 frames). We therefore took advantage of 'motion blurring' when recording 500 ms trajectories (see below) to detect only chromatin bound proteins 1,46 , and combined this with time-lapse imaging for different lengths of time, in an attempt to determine the dissociation time of the NuRD complex. To our surprise this showed that the dissociation times were much longer than we expected (greater than 100 seconds for MBD3, Extended Data Figure 9d), such that it proved impossible to track individual molecules for long enough in order to determine reliable rates.…”
Section: Chromatin Association Of the Deacetylase Sub-complex Requirementioning
confidence: 99%